Corporate income taxes and entrepreneurship - Jörn Block (IZA World of Labor, 2016)
Corporate income taxation influences the quantity and type of entrepreneurship, which in turn affects economic development. Empirical evidence shows that higher corporate income tax rates reduce business density and entrepreneurship entry rates and increase the capital size of new firms. The progressivity of tax rates increases entrepreneurship entry rates, whereas highly complex tax codes reduce them. Policymakers should understand the effects and underlying mechanisms that determine how corporate income taxation influences entrepreneurship in order to provide a favorable business environment.
Keywords: L26; H25; 330; entrepreneurship; self-employment; start-ups; business taxes; corporate income taxes